The Art of Compromise: Belgium as the Bridge between Germany and France. Issue 2 (3rd April 2022) - Chang, Michele
Abstract : This contribution applies the theoretical framework developed by Schoeller and Falkner (this issue) to the case of Belgium. First, it examines Belgium's preferences and the status quo before and after the financial crisis, juxtaposed against Germany's preferred outcomes. Belgium has traditionally favoured more integration, leading to Belgium's strategy of co-shaping and pace-setting in regards to monetary integration through persuasion, cultivating alliances, and brokering compromises that satisfied Germany's interests in EMU versus those of the European Commission and France. The global financial crisis changed Belgium's strategy, as it became constrained by the effects of the crisis on its economy and the domestic political turmoil that ensued. Belgium went from a pre-crisis pace-setter to a fence-sitter, relying on the persuasion of its allies to convince Germany to agree to reform the architecture of euro area governance. Finally, this contribution considers the institutional fabric of Belgium's relation to the hegemon. This is relatively weak between Belgium and Germany, making multilateral settings the preferred forum rather than bilateral. Nevertheless, Belgium's famous capacity for forging compromises among disparate interests was demonstrated through the diplomacy of former Belgian Prime Minister Herman Van Rompuy as the European Council's first full-time president.